Hypocenter relocations and tsunami simulation for the 15 November 2014 Northern Molucca Sea earthquake in Indonesia - Aditya Riadi Gusman; Andri D. Nugraha; Hasbi Ash Shiddiqi (Jurnal Geofisika, 2017)
A reverse fault earthquake (Mw 7.1) occurred in the Northern Molucca Sea, Indonesia, on 15 November 2014 at 2:31:40 UTC. The earthquake produced small tsunami waves that are recorded at Jailolo (9 cm), Tobelo (1 cm), and Menado (3 cm) tide gauges. The Indonesian Agency for Climatology, Meteorology, and Geophysics (BMKG) issued a timely (5 minutes after the earthquake) tsunami warning for the event. We used the teleseismic double‐difference seismic tomography method (teletomoDD) to relocate the hypocenters of the mainshock and the aftershocks. The relocated hypocenter of the mainshock for the 2014 Northern Molucca Sea earthquake is located at 1.923°N, 126.539°E, and depth of 48.87 km. In general, the relocated aftershock hypocenters are shallower than those from the BMKG catalog. The relocated hypocenters are distributed within a depth range of 6 to 64 km. The aftershock area from the relocated hypocenters is 80 km long and 55 km wide. The estimated seismic moment from the Global CMT solution (GCMT) was 4.75 × 1019 Nm. We simulated the tsunami from fault model of each GCMT nodal plane to find a fault model that can best explain the observed tsunami heights at Jailolo, Tobelo, and Menado tide gauges. The best single fault model for this event is dipping to the west, has fault length, width, and slip amount of 47 km, 25 km, and 1.16 m, respectively. The K value calculated using the observed and simulated tsunami heights for this best model is 1.026, suggests a very good fit to tsunami observations.